XCL1, a serum biomarker in neurological diseases; HTLV-1-associated myelopathy and multiple sclerosis. (January 2023) - Saeidi, Morteza; Vahidi, Zohreh; Nahayati, Mohammad Ali; Rezaiyan, Majid Khadem; Zemorshidi, Fariba; Mahdifar, Maryam; Hafezi, Fatemeh; Moghadam, Saeedeh Mehraban; Saghi, Effat; Akbarpour, Ensieh; Boostani, Reza; Rafatpanah, Houshang
Abstract: The XCL1-XCR1 axis has a potential role in the recruitment of immune cells to the site of inflammation. The present study aimed to examine the relation of XCL1 serum levels with Multiple sclerosis (MS) and HTLV-1-associated myelopathy (HAM), as chronic inflammatory diseases of the central nervous system (CNS). DNA was extracted to evaluate HTLV-1 proviral load (PVL) using real-time PCR. Serum levels of XCL1 was determined by using an ELISA assay. The serum level of XCL1 was significantly higher in patients with HAM than that of asymptomatic carriers (ACs) and healthy controls (HCs) (p < 0.001 and p < 0.0001, respectively) and was also higher in MS patients compared to HCs (p < 0.0001). Moreover, the concentration of XCL1 serum level was significantly different between the ACs and HCs group (p < 0.0001). In conclusion, increased expression of XCL1 might contribute to the migration of autoreactive T cells to the central nervous system and play a critical role in the development and pathogenesis of inflammatory neurological diseases including HAM and MS. Highlights: XCL1 seems to play a role in the inflammation of the CNS in MS and HAM. XCL1 has high serum levels in MS and HAM patients. XCL1 might participate in directing cell migration into the CNS and induction of the inflammatory response in MS and HAM.